Hubungan Komunikasi Efektif Terhadap Kepuasan Pasien di Apotek K24 Vienna Gading Serpong - Melizsa Melizsa (Jurusan Farmasi, Poltekkes Kemenkes Palembang, 2023)
Background Effective communication is a problem for Indonesians today, there are still many who are unfamiliar with the culture of Effective communication and lack of listening skills in communicating, which causes them to have more opinions to raise problems than to think about solving problems. Patient satisfaction is one of the important indicators that must be considered in health services. Pharmacy is one of the fields of health services that provide satisfaction to customers. Health services are every effort that is carried out alone or simultaneously within an organization to maintain and improve health, prevent and cure diseases and restore the health of individuals, families, groups and or communitie. Research purposes to find out the Relationship of Effective Communication to Patient Satisfaction at Apotek K24 Vienna Gading Serpong. Research methods used in this study is a quantitative method with a cross sectional design, the sampling technique applied is accidental sampling, the population is 5029 patients with a sample of 100 respondents. Research result the value of the effective communication variable obtained 4.04 which means very good and the patient satisfaction variable obtained 4.03 which means very satisfied.There is a significant relationship between effective communication and patient satisfaction (rcount 0.837 > rtable 0.195).Conclusion effective communication variables and patient satisfaction get very good and very satisfied scores, there is a very strong relationship on the variables and indicators of effective communication (affecting attitudes) on patient satisfaction (assurance).